The Interaction Of Renin-Angiotensin And Sympathetic Nervous Systems In Diabetes And Hypertension - Lazhari, Mohamed Ibrahim A. Ali (2004)
Sympathetic overactivity is considered to be an important factor in the pathogenesis of hypertension. An increase in sympathetic nervous system activity causes an increase in blood pressure and contributes to the development and maintenance of hypertension through stimulation of the heart, peripheral vasculature and kidneys. This study was designed to evaluate the effect of c1onidine, clonidine analogue, AL12 and ACE inhibitor, perindopril in modulating pressor responses elicited by a set of exogenous adrenergic agonists and Ang II in normal and animals with diabetes and hypertension. Further attempt was made to determine any possible interaction ofRAS and sympathetic system at the peripheral level in these animals. The animals were divided into several groups depending on the treatments used. Clonidine, AL12 and perindopril were administered once daily through oral gavage at dose of O.OSmg/kg, 10mg/kg and 2mg/kg respectively for six consecutive days. The control groups received either saline or tween 80 depending on their use as vehicle in preparation of these drugs. Metabolic data were collected on every alternate day and animals were subjected to acute study on day 7. In acute studies, the animals were anaesthetized (sodium pentobarbitone 60mglkg i.p) and tracheotomy was done. The left carotid. artery was cannulated to measure blood pressure and left jugular vein was cannulated for continuous infusion of anesthesia (12.5 mg/kg/hr) and also to infuse vasoconstrictor agents i.e. noradrenaline (200, 400 and 800 ng/ml), phenylephrine (2, 4 and 8 ug/ml) and angiotensin II (5, 10 and 20 ng/ml). The changes in pressor responses elicited by adrenergic agonists and Ang II were recorded in terms of changes in blood pressure. All data were expressed as mean ± s.e.m and compared with 2 way ANOVA followed by Duncan's post-hoc test with significance level of 5%. In metabolic study, it was observed that clonidine produced diuresis and natriuresis in all experimental groups whereas perindopril could not produce such effects. In the study with clonidine analogue, it was observed that its diuretic effect might have different mechanism of action as compared to clonidine and other well known clonidine analogues. However, the effect of ALl2 on natriuresis was comparable to clonidine, hence indicating a possible similar mode of action.